Associations between psychosocial burden and prognostic biomarkers in patients with stable coronary heart disease – a STABILITY substudy. (25th November 2020) - Wassberg, C; Batra, G; Hadziosmanovic, N; Hagstrom, E; White, H; Stewart, R; Siegbahn, A; Wallentin, L; Held, C
Abstract: Background: Psychosocial burden is associated with increased risk of cardiovascular (CV) events in patients with stable coronary heart disease (CHD). The underlying mechanisms linking psychosocial burden and CHD are unclear and might be explained by studying biomarkers known to be associated with CV risk. Methods: 15, 608 patients in the STABILITY trial completed a questionnaire on to what extent they were feeling down, had loss of interest, experienced financial stress and if they were living alone. Levels of high-sensitivity (hs) C-reactive protein (hs-CRP), interleukin-6 (IL-6), hs-troponin T (hs-TnT) and N-terminal pro-B type natriuretic peptide (NT-proBNP) were assessed at baseline. Associations between levels of psychosocial burden (sometimes, often/always vs. never/rarely) and biomarkers were evaluated in a linear model where geometric mean ratio of the log-transformed biomarker were calculated. Results: Adjusted associations (age, gender and established CV risk factors) are presented in the table. Conclusion: Psychosocial burden in patients with stable CHD was independently associated with elevated biomarkers. The underlying association is likely to be complex and involve multiple pathways. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): The STABILITY study was funded by GlaxoSmithKline. Roche Diagnostics, Rotkreuz, Switzerland, supported the research by providing the GDF-15 assay free of charge.